A. \(S=\{\frac{1}{2};-1\}\)
B. \(S=\{-\frac{1}{2};\frac{9}{4}\}\)
C. \(S=\{\frac{1}{2}\}\)
D. \(S=\{-\frac{1}{2}\}\)
C
ĐK: \(5-3 x \geq 0 \Leftrightarrow x \leq \frac{5}{3}\)
Khi đó phương trình trở thành
\(\left[\begin{array}{l} x-4=5-3 x \\ x-4=-(5-3 x) \end{array} \Leftrightarrow\left[\begin{array}{l} 4 x=9 \\ 2 x=1 \end{array} \Leftrightarrow\left[\begin{array}{l} x=\frac{9}{4}(\text { loai }) \\ x=\frac{1}{2} \end{array}\right.\right.\right.\)
vậy \(S=\{\frac{1}{2}\}\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247